Climatic trends of extreme wave events caused by Arctic Cyclones in the western Arctic Ocean - Waseda, Takuji; Nose, Takehiko; Kodaira, Tsubasa; Sasmal, Kaushik; Webb, Adrean (Polar Science, 2021)
The sea ice coverage in the summer Arctic Ocean from the Beaufort to Laptev Seas continues to decrease, and the largest waves in the western Arctic open waters are increasing year by year. By looking into the historical wave events in the ERA-Interim reanalysis data, we discovered that more than half of the extreme events are caused by cyclones that are originating in the Arctic Ocean as well as in the mid-latitudes. During September, when the ice-free water area becomes largest each year, the percentage of extreme events caused by cyclones has increased from around 50% to almost 80% in the last four decades. Moreover, the locations of these extreme events are spreading from the Chukchi Sea to the east and west along the coasts and towards the central Arctic Ocean as depicted in the characteristic changes of the probability of sea states over the past decades. These findings are pertinent for safe navigation along the Northern Sea Route. journal article